Perfilamento de impurezas em amostras de ecstasy apreendidas em Minas Gerais utilizando microextração em fase sólida e análise por cromatografia gasosa acoplada à espectrometria de massas - Bernardo Schmitberger Moraes (2022)
The active ingredient of street drug ecstasy, 3,4-methylenedioxymethamphetamine (MDMA), is generally synthesized under little or no hygiene and purifications protocols, and thus a number of impurities, such as byproducts and intermediates is carried over to the final product – the tablet. To collect data on these impurities is called chemical profiling, which is a powerful tool to aid law enforcement in fighting drug trafficking. In the present work, 89 street samples, seized by Civil Police of Minas Gerais, were prepared by a harmonized method described in the literature, and analyzed by gas chromatography coupled to mass spectrometry. Out of these samples, 38 were prepared by direct immersion solid-phase microextraction (DI-SPME), with a divinylbenzene-polydimethylsiloxane-coated fiber, to evaluate this technique’s feasibility, whose parameters were optimized by a multivariate design. In total, 72 different chemical species were detected in the 89 samples; principal component analyses, hierarchical cluster analyses and correlation metrics were performed. Profiling by the harmonized method revealed similarities among samples whose tablets were physically different, which would go unnoticed in routine analyses. It also showed that samples with nearly identical tablets can have different origins. Besides that, it was noticed a unusually high content of 3,4-methylenedioxyphenylpropan-2-ol, a MDMA synthesis byproduct, in some samples. Some synthesis route-specific compounds were also detected in certain samples. Regardind the DI-SPME optimization, four factors were relevant: pH, desorption time, sample mass and extraction time. DI-SPME proved itself promising in the context of profiling by providing results comparable to those of the harmonized method. In all cases, relative standard deviation and retention time shift were acceptable. It was concluded that profiling is a promising tool in fighting drug trafficking in Brazil.